Numerical Analysis Results of Debonding Damage Effects for an SHM System Application on a Typical Composite Beam - Gianluca Diodati; Assunta Sorrentino; Lorenzo Pellone; Antonio Concilio; Monica Ciminello; Gianvito Apuleo; Shay Shoham; Iddo Kressel; David Bardenstein (Aerospace, 2023)
In the aeronautical field, the damage that occurs to a carbon-fibre-reinforced polymer (CFRP) structure analysis is a crucial point for further improving its capability and performance. In the current the state of the art, in fact, many issues are linked to the certification process more than to technological aspects. For the sake of clarity, it should be added that regulations call for technological solutions that are invasive (in terms of weight and manufacturing costs) or exploit technologies that are not fully mature. Thus, the truth is in between the above statements. One of the possible solutions to bypass this issue is the assessment of a structural health monitoring system (SHM) that is sufficiently reliable to provide a full-state representation of the structure, automatically, perhaps in real-time, with a minimum intervention of specialized technicians, and that can raise an alert for safe maintenance whenever necessary. Among the different systems that have been proposed in the scientific and technological literature, SHM systems based on strain acquisitions seem very promising: they deduce the presence of flaws by analysing the variations of the intimate response of the structure. In this context, the SHM using fibre optics, supported by a dedicated algorithm, seems to be able to translate the effects of the damage reading the strain field. This means that is necessary to have a full comprehension of the flaws’ effects in terms of strain variation to better formulate a strategy aimed at highlighting these distortions. It should be remarked that each type of damage is distinct; imperfections of the bonding line are herein targeted since the quality of the latter is of paramount importance for ensuring the correct behaviour of the referred structure. This presents paper focuses on a deep investigation on the strain field peculiarities that arise after the imposition of irregularities in the adhesive region. The aim is to explore the damage dimension versus its effect on the strain map, especially when bonding connects different parts of a complex composite beam. By means of finite element method applied on a typical aeronautical beam, a parametric numerical simulation was performed in order to establish the influence of a debonding dimension on a reference strain map. This work provides evidence that these effects on strain flaw decrease the distancing itself of the damage. The knowledge of these effects can be highly helpful during the design of a preliminary phase of an SHM system in order to choose the most suitable sensor in terms of reading sensitivity error, the number to be used, and their location.